Murphy’s Canon: Leadership in the Age of Uncertainty - Forbes, Raymond L. (Advances in Social Sciences Research Journal, 2025)
How might the nefarious “Murphy’s Law,” allegedly created by a disgruntled American aerospace engineer in the 1950s, apply in today’s chaotic world? Just how applicable is the law now in a new era that has been characterized by the descriptive label of FUD, or Fear, Uncertainty, and Doubt? This paper will explore the infamous Murphy adage, as well as describe who Murphy was and how he came to formulate his cheeky directive. Additionally, this piece will expand on Murphy’s original provocative rule, feature several versions of it, provide alternative formulations, and discuss how the law might be reinterpreted to more currently apply. It will also offer an updated set of canons that may be more appropriate to this historical time and place. This article will also provide like-minded parallels to the ongoing revolution in leadership thinking that has occurred since Murphy first offered his dark humor observations on the world of work. In addition, this paper will note some key “then and now” differences from a practicing leader’s perspective, and conclude with a discussion of key findings, strategies for improvement and consider the value of balancing optimism and realism in a time of pron0unced uncertainty.